Fibrolytic enzymes improving in vitro rumen degradability of tropical forages - Sakita, Gabriel Zanuto; Ventoso Bompadre, Thiago Francisco; Dineshkumar, Dhanasekaran; Tavares Lima, Paulo de Mello; Abdalla Filho, Adibe Luiz; Campioni, Tania Sila [UNESP]; Oliva Neto, Pedro de [UNESP]; Bremer Neto, Herman; Louvandini, Helder; Abdalla, Adibe Luiz (Wiley-Blackwell, 2020)
During specific times of the year, especially dry seasons, tropical forages typically have poor nutritional value due to high contents of neutral and acid detergent fibres, and low crude protein in their composition, which may reduce productivity of ruminant livestock production and lead to increased enteric methane (CH4) emissions per unit of generated product in forage-bases systems. In order to increase fibre degradability and the efficiency of energy utilisation from low-quality forages, exogenous fibrolytic enzymes have been studied. In this assay, we evaluated the effects of increasing dose levels of fibrolytic enzymes extract (FEE) produced by Trichoderma reesei on in vitro rumen organic matter degradability, fermentation parameters, total gas and CH4 production of tropical forages. Forage samples were analysed for their bromatological composition, and enzyme activity from FEE was performed for xylanase and endoglucanase. The in vitro gas production technique was used in a 5 x 3 factorial arrangement with five FEE dose levels (0, 5, 50, 500 and 5,000 mu l) and three substrates (Cynodon spp., Panicum maximum and Cenchrus ciliaris L.). The highest dose level of FEE increased degradability, total gas and CH4 production in all substrates (p < .05). Butyrate concentration also increased while acetate:propionate ratio and pH decreased with the addition of FEE (p < .05). These results indicated that the use of fibrolytic enzymes can be a reliable strategy to improve degradability of low-quality forages, contributing to the sustainability and intensification of livestock production in tropical countries.
Keywords: enteric methane; fermentation; fibre degradability; gas production; grass-fed production; ruminants